Dynamic instability in neuronal microtubules. (2020) - Priya, R.; Kavitha, L.; Gopi, D.
Abstract: The Hamiltonian describing the interaction between the two neighbouring filaments of neuronal microtubules (nMTs) and in addition of u and ф model, which may be represented as longitudinal and radial displacements. From this Hamiltonian, we get discrete Nonlinear Schrodinger (DNLS) like equations by using the Rotating wave approximation (RWA). In order to analyze the instability nature of the system, we perform modulational instability (MI) analysis for the DNLS equations of motion which attribute for the energy localization phenomenon and it paves way for bio-energy transport in intracellular communications.